THE EFFECT OF FINANCIAL RATIOS ON FINANCIAL DISTRESS (EMPIRICAL STUDY OF HOTEL AND TOURISM SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD) - Febiyanti Kusuma Dewi; Bambang Sudiyatno (Jurnal Ekonomi, 2023)
This study aims to examine the effect of financial ratios, including liquidity ratios, profitability, leverage, activity, and sales growth on financial distress in hotel and tourism sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The data used is secondary data in the form of financial statements and annual reports for 2017-2021. Technical data analysis uses multiple linear regression analysis. Sampling was carried out by purposive sampling with a total sample of 21 companies from a total population of 33 companies, then the number of observations was 105. The research findings show that liquidity and leverage variables have a significant positive effect on financial distress, profitability variables have a significant negative effect on financial distress, activity variables and sales growth do not have a positive effect on financial distress.